Positive reaction in mouse ligated intestinal loop assay with nonenterotoxigenic and nonhemolytic strains of Staphylococcus aureus. - Sakaguchi, T (1988)
Nonenterotoxigenic and nonhemolytic strains of Staphylococcus aureus exhibited a positive reaction in the mouse intestinal loop assay except for a strain negative for the egg yolk reaction. Edema and swelling in all positive loops, increased bacterial cell numbers within intestinal loops, and extremely close adhesion to or inclusion of numerous bacterial cells in HeLa cells after inoculation of the strains were observed. These results suggest a possible invasive ability of the strains.